Boolean Algebra Proof (Distribution and XOR)

In summary: A*A = A ##.In summary, using the definition of exclusive or (XOR), the commutative and associative properties of XOR, and other Boolean algebra theorems, it can be proven that A*(B (XOR) C) is equal to (A*B) (XOR) (A*C). This is done by manipulating the expressions and applying DeMorgan's Rule.
  • #1
PhotonSSBM
Insights Author
154
59

Homework Statement


Use the definition of exclusive or (XOR), the facts that XOR commutes and
associates (if you need this) and all the non-XOR axioms and theorems you know
from Boolean algebra to prove this distributive rule:

A*(B (XOR) C) = (A*B) (XOR) (A*C)

Homework Equations


All the boolean algebra theorems

The Attempt at a Solution


So here's what I've tried

A*(B (XOR) C)
=A*B*C' + A*B'*C
=A*X+A*X'
=A*1
=A*(X (XOR) X')

And

(A*B) (XOR) (A*C)
=A*B*(A*C)' + (A*B)'*B*C
=A*B*(A' + C') + (A' + B')*B*C
=A*B*A' + A*B*C' + A'*B*C + B'*B*C
=A*B*C' + A'*B*C
=B*(A (XOR) C)
I feel like I go in circles no matter what I do.
Any clues?
 
Physics news on Phys.org
  • #2
PhotonSSBM said:
=A*X+A*X'
This looks wrong. :))
PhotonSSBM said:
=A*B*(A*C)' + (A*B)'*B*C
Mistake here, too. :H
 
  • Like
Likes PhotonSSBM
  • #3
Oops, that's not how demorgans works...brb with corrections.
 
  • #4
Ok, the answer came out once I realized how to use DeMorgan's Rule for the right hand side:

(A*B) (XOR) (A*C)
=(A*B) * (A*C)' + (A*B)' * (A*C)
=A*B * (A' + C') + (A' + B') * A*C
=A*A'*B + A*B*C' + A'*A*C + B'*A*C
=A*B*C' + A*B'*C
=A*(B*C' + B'*C)
=A* [B (XOR) C]

Thanks for the help!
 
Last edited:
  • #5
in the next step:
=A*A'*B + A*B*C' + A'*A*C + B'*A*C
=A*B*C' + A*B'*C

what happened with (A*A'*B + A'*A*C)?
 
  • #6
Hi,

Raimundo said:
what happened with (A*A'*B + A'*A*C)?

I think those go to zero as ## A \cdot \bar A = 0 ##
 
  • Like
Likes Raimundo

Similar threads

Back
Top